PLACES AND NAMES IN ASŪNE PARISH IN THE CENSUS (“REVISION OF SOULS”) OF 1772 - Kovaļevska, Otīlija (Via Latgalica, 2017)
The aim of the article is to present the content of the census 1772 for Rēzekne District and show the possibilities it provides for research of the place names of certain areas. The chosen territory corresponds to Asūne parish as it was in 1935 and includes the contemporary Asūne and Ķepova parish, as well as partially Svariņi and Bērziņi parish. The results of 1772 census is the richest source of information about villages and inhabitants which belonged to the former Asūne half a manor and clergy house in 18th century. The documents describe 75 villages, 424 households and 4733 persons. Individual people are listed indicating each person’s name, surname (for adults), age, and position in the family or kinship (hosts, wives, children, other relatives, foster children, workers s. c.). Up to now it is also the oldest source, so broadly representing women's surnames in Asūne parish because they differ from their husbands' surnames. Most often a woman kept their father’s surname, but occasionally the surname was made of her father’s name or even of a place name. Thereby it becomes possible to observe the intense formation process of surnames and related place names in the 18th century. Noteworthy are the names and surnames that are rare or even have not survived to the present day, but the traces of such names are still preserved in place names and surnames, which in turn indicate newcomers from other parishes and even from Belarus. Geographical descriptions of villages contain also the names of 17 lakes and 11 rivers; most of them have kept their names until nowadays. Older forms of actual place names and several already disappeared names can be found there.For the analysis of the material options of Excel programs (structuring, selection the materials, extraction and processing of statistical data, graphic visualization) have been used. Cartographical methods have been employed to search for correlations between the village names and surnames. To acquire a better understanding of the results of the census 1772, these materials were compared with earlier 18th century census data, as well as with maps from various periods.